Constructing Polymorphic Nanodomains in BaTiO3 Films via Epitaxial Symmetry Engineering. (24th February 2020) - Peng, Wei; Zorn, Jacob A.; Mun, Junsik; Sheeraz, Muhammad; Roh, Chang Jae; Pan, Jun; Wang, Bo; Guo, Kun; Ahn, Chang Won; Zhang, Yaping; Yao, Kui; Lee, Jong Seok; et al.
Abstract: Ferroelectric materials owning a polymorphic nanodomain structure usually exhibit colossal susceptibilities to external mechanical, electrical, and thermal stimuli, thus holding huge potential for relevant applications. Despite the success of traditional strategies by means of complex composition design, alternative simple methods such as strain engineering have been intensively sought to achieve a polymorphic nanodomain state in lead‐free, simple‐composition ferroelectric oxides in recent years. Here, a nanodomain configuration with morphed structural phases is realized in an epitaxial BaTiO3 film grown on a (111)‐oriented SrTiO3 substrate. Using a combination of experimental and theoretical approaches, it is revealed that a threefold rotational symmetry element enforced by the epitaxial constraint along the [111] direction of BaTiO3 introduces considerable instability among intrinsic tetragonal, orthorhombic, and rhombohedral phases. Such phase degeneracy induces ultrafine ferroelectric nanodomains (1–10 nm) with low‐angle domain walls, which exhibit significantly enhanced dielectric and piezoelectric responses compared to the (001)‐oriented BaTiO3 film with uniaxial ferroelectricity. Therefore, the finding highlights the important role of epitaxial symmetry in domain engineering of oxide ferroelectrics and facilitates the development of dielectric capacitors and piezoelectric devices. Abstract : A polymorphic nanodomain structure with coexistent metastable tetragonal, orthorhombic, and rhombohedral phases is constructed in BaTiO3 films by growing on SrTiO3 (111) substrates. The domain state results from a threefold rotational symmetry around the surface normal of the substrate imposed on inherently tetragonal BaTiO3 . Consequently, (111)‐oriented BaTiO3 films yield significantly enhanced dielectric and piezoelectric responses compared to the (001)‐counterpart.